Electronic interference transport and its electron–phonon interaction in the Sb-doped Bi2Se3 nanoplates synthesized by a solvothermal method. (2nd November 2015) - Zhao, Bo; Chen, Taishi; Pan, Haiyang; Fei, Fucong; Han, Yuyan
Abstract: Here we synthesized the antimony doped nanoplates by the solvothermal method. The angle-dependent magnetoconductance study was carried out and all the were found to be normalized to the perpendicular field, indicating a clear 2D electronic state. The features of weak antilocalization and universal conductance fluctuations were clearly identified in the magnetoresistance transport of the 4-probe nanodevices. The dephasing lengths are extracted respectively according to the Hikami–Larkin–Nagaoka theory. It is attributed to the involvement of the dynamic spin centers. The dephasing lengths are found to increase with the decreasing temperature following a law with . This reveals the additional dephasing source of electron–phonon interaction, which is often absent for pure 2D electronic systems.